The Influence of Sakip Guidelines and Local Government Commitment on the Effectiveness of the Implementation of Sakip Mediated By Work Culture in Sidoarjo Regency - Febriantoro, Yoga; Sari, Rida Perwita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to examine the influence of SAKIP guidelines and local government commitments on the effectiveness of SAKIP implementation, with work culture as a mediation variable in Sidoarjo Regency. In this study, a quantitative method was used by collecting data through questionnaires distributed to officials in the Sidoarjo Regency office, including the head of the office, the secretary of the office, the head of the planning and finance sub-division, and the staff of the planning and finance section. The results of the data analysis show that the SAKIP guidelines, local government commitment, and work culture have a significant positive effect on the effectiveness of the implementation of SAKIP. In addition, it was found that bydaya daya was able to mediate the relationship between the SAKIP guidelines and the commitment of local governments and the effectiveness of SAKIP implementation. The implications of this study emphasize the importance of local governments not only to strengthen their commitment to SAKIP, but also to develop a supportive work culture. Leadership training programs, performance incentives, and regular evaluations of the implementation of SAKIP are recommended to increase the effectiveness of SAKIP implementation.